History, propaganda, and glory in the early Dominican chronicles of the Philippines - Jorge Mojarro (Nuevas de Indias)
During the first century of the Dominican presence in the Philippines, their chroniclers -Aduarte, Santa Cruz, De Los Ángeles and De Paula, and Peguero- wrote four histories of the Province of the Holy Rosary. Although only two were finally printed, the chronicles served as essential discursive tools to propagandize their achievements in far-away missions. Without exception, all missionary orders engaged in producing these complex texts, which formed part of the typical literary genres of colonial literature. The historical nature of ecclesiastical chronicles fluctuated between furnishing exact information and omitting specific facts while displaying certain narrative strategies that served the ultimate goal of the Dominican friars. This paper will analyze the structure of these chronicles, their contextual history, and the particular rhetoric they engaged in as they presented the Christianization of the inhabitants of the Philippines under their religious jurisdiction.